Management and outcome of hepatic artery thrombosis after pediatric liver transplantation. (12th December 2020) - Channaoui, Aniss; Tambucci, Roberto; Pire, Aurore; de Magnée, Catherine; Sokal, Etienne; Smets, Françoise; Stephenne, Xavier; Scheers, Isabelle; Reding, Raymond
Abstract: Background: Pediatric LT are at particular risk of HAT, and its management still constitutes a matter of debate. Our purpose was to study predisposing factors and outcome of HAT post‐LT, including the impact of surgical revisions on survival and biliary complications. Methods: Among 882 primary pediatric LT performed between 1993 and 2015, 36 HAT were encountered (4.1%, 35 fully documented). Each HAT case was retrospectively paired with a LT recipient without HAT, according to diagnosis, age at LT, type of graft, and era. Results: Five‐year patient survivals were 77.0% versus 83.9% in HAT and non‐HAT paired groups, respectively ( P  = .321). Corresponding graft survivals were 20.0% versus 80.5% ( P  < .001), and retransplantation rates 77.7% versus 10.7%, respectively ( P  < .001). One‐year biliary complication‐free survivals were 16.6% versus 83.8% in the HAT and non‐HAT groups, respectively ( P  < .001). Regarding chronology of surgical re‐exploration, only HAT cases that occurred within 14 days post‐LT were re‐operated, fourteen of them being explored within 7 days post‐LT (revascularization rate: 6/14), versus two beyond 7 days (no revascularization). When revascularization was achieved, graft and biliary complication‐free survival rates at 1 year were 33.3% and 22.2%, respectively, both rates being 0.0% in case of failure. Conclusions: The pejorative prognosis associated with HAT in terms of graft survival is confirmed, whereas patient survival could be preserved through retransplantation. Results suggest that HAT should be re‐operated if occurring within 7 days post‐LT, but not beyond.